The Residues AGDV of Recombinant γ Chains of Human Fibrinogen Must Be Carboxy-Terminal to Support Human Platelet Aggregation - Hettasch, Joann M; Bolyard, Mark G; Lord, Susan T (Thrombosis and Haemostasis, 1992)
The carboxy-terminus of the γ chain of fibrinogen contains a sequence which is believed to be one of the domains that interacts with glycoprotein (GP) IIb/IIIa to support platelet aggregation. A normal variant of fibrinogen exists in which the four carboxy-terminal amino acids are replaced by 20 amino acids. This variant, known as γ’, has been reported to bind less effectively to platelets. The purpose of the present study was to engineer novel proteins to determine what differences in amino acid sequence between the γ and γ’ chains influence the interaction of the carboxyterminus with GPIIb/IIIa. In this regard, the γ chain cDNA in a bacterial plasmid expression vector was modified by oligonucleotide-directed mutagenesis to produce recombinant γ chains with amino acid changes in the carboxy-terminus which reflect the differences between γ and γ’. The recombinant γ chain with an unmodified carboxy-terminus supported adenosine diphosphate (ADP)-induced platelet aggregation to the same extent as intact fibrinogen. In contrast, the ability of γ’ 427 (the recombinant γ’ variant) and γ 427 (where the 16 amino acid γ’ extension [412–427] was added to the carboxy-terminus of γ) to support platelet aggregation was markedly reduced. In addition, the extent of ADP-induced platelet aggregation was decreased in the presence of γ’ 411 (where amino acids 408–411 in γ were replaced with amino acids 408–411 in γ’), while γ 407 (where the four carboxy-terminal amino acids were deleted) was not capable of supporting aggregation. These findings demonstrate that the four residues AGDV are not only required but must be carboxy-terminal to support platelet aggregation.